This man's pill - Djerassi, Carl (Oxford University Press, 2001)
On October 15, 1951, in a small laboratory in Mexico City, one of the key episodes in 20th century social history occurred: the first synthesis of a steroid oral contraceptive--an event that triggered the development of the Pill. Carl Djerassi has been honored worldwide for that accomplishment, which ultimately changed the life of women and the nature of human reproduction in ways that were not then foreseeable